2012
DOI: 10.1002/jssc.201100733
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and application of a new 25,27‐bis‐[2‐(5‐methylthiadiazole)thioethoxyl]‐26,28‐dihydroxy‐para‐tert‐butyl calix[4]arene stationary phase for HPLC

Abstract: A new para-tert-butylcalix[4]arene column containing thiadiazole functional groups was prepared and used for the separation of polycyclic aromatic hydrocarbons, phenolic compounds, aromatic amines, benzoic acid and its derivatives by high-performance liquid chromatography (HPLC). The effect of organic modifier content in the mobile phase on retention and selectivity of these compounds were investigated. The results indicate that the stationary phase behaves like reversed-phase packing. However, hydrogen bondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…There are a number of selective factors in the configuration of calixarenes such as cavity size, conformation, and substituents. Since Glennon and his co-workers reported the application of calixarenes as the stationary phase, it has attracted extensive attention. Our group has been comitted to the research of calixarene stationary phases for many years, and a novel multi-interaction and mixed-mode stationary phase based on tetraazacalix[2]arene[2]triazine modified silica gel (NCS, Figure ) has been synthesized in our laboratory in 2012 . Being different from conventional calixarenes in which the aromatic rings are linked by methylene units, tetraazacalix[2]arene[2]triazine assembles aromatic rings by −NH– and adopts a 1,3-alternate conformation with two benzene rings nearly face-to-face parallel and two triazine rings tending to an edge-to-edge orientation in the solid phase.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of selective factors in the configuration of calixarenes such as cavity size, conformation, and substituents. Since Glennon and his co-workers reported the application of calixarenes as the stationary phase, it has attracted extensive attention. Our group has been comitted to the research of calixarene stationary phases for many years, and a novel multi-interaction and mixed-mode stationary phase based on tetraazacalix[2]arene[2]triazine modified silica gel (NCS, Figure ) has been synthesized in our laboratory in 2012 . Being different from conventional calixarenes in which the aromatic rings are linked by methylene units, tetraazacalix[2]arene[2]triazine assembles aromatic rings by −NH– and adopts a 1,3-alternate conformation with two benzene rings nearly face-to-face parallel and two triazine rings tending to an edge-to-edge orientation in the solid phase.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Hu et al reported a new 25,27-bis-[2-(5-methylthiadiazole)thioethoxyl]-26,28-dihydroxy-para-tert-butyl calix [4]arene stationary phase for the separation of aromatic amines and anilines. 25 These results conrm the usability of reversephase packing with inclusion capability of calixarene-bonded stationary phases.…”
Section: Introductionmentioning
confidence: 90%
“…By modifying them onto the surface of silica gel, calixarenes have been widely studied as solid phase extraction and stationary phase materials. Due to the peculiar structural characteristics of cavity-shape and benzene ring skeleton, these materials can offer varieties of interaction with analytes, such as hydrophobic, hydrogen bonding, π - π , as well as inclusion interaction [2331]. Nowadays, heterocyclic calixarene appeared as a novel kind of supramolecular compound [32].…”
Section: Introductionmentioning
confidence: 99%